Wide Angle Phase only Computer Generated Hologram by Angular Spectrum Compact Space Bandwidth product method - Szawerdak, Artur; Ciesielski, Dawid; Kozacki, Tomasz (Photonics Letters of Poland, 2026)
Wide-angle capability is critical for holographic near-eye displays. Since most systems employ phase-only spatial light modulators (SLMs), computer-generated holograms (CGHs) must be encoded as phase-only holograms (PoHs). This work presents two approaches for PoH-based CGH generation from plane images: a direct single-step method (D-PoH) and an iterative method (I-PoH). Both utilize the Compact Space-Bandwidth Angular Spectrum (CSW-AS) technique for propagation, which is optimal for wide-angle scenarios. We evaluate their accuracy and zero-padding requirements. Results show that I-PoH provides a higher quality image, but at the cost of cyclic computations and the requirement of substantially larger zero-padding compared to D-PoH, limiting its efficiency for wide-angle applications. In contrast, I-PoH achieves a maximum field of view (FoV) of 39°, while D-PoH enables a significantly larger FoV of 54°, for a PC with 64GB RAM. These findings demonstrate the advantage of direct single-step encoding for achieving wide-angle holographic displays. Full Text: PDF References O. Mendoza-Yero, G. Mínguez-Vega, and J. Lancis, "Encoding complex fields by using a phase-only optical element", Opt. Lett. 39(7), 1740 (2014). CrossRef Y. Qi, C. Chang, and J. Xia, "Speckleless holographic display by complex modulation based on double-phase method", Opt. Express 24(26), 30368 (2016). CrossRef A. Szawerdak, R. Kukolowicz, M. S. Idicula, M. Chlipala and T. Kozacki, "Phase-only encoding of wide-angle 3D computer generated hologram", Photonics Letters of Poland, 17(2), 60-63 (2025). CrossRef T. Gu, C. Han, H. Qin, K. Sun, "Phase-only hologram optimization with adaptive constraint strategy for high-quality optical reconstruction", Opt. Express, 32(25), (2024). CrossRef S. J. Liu, L.F. Feng, S. J. Ji, H. N. Yan, K. Yang, P. P. Li, D. Wang, "Speckle noise suppression method in holographic display using optimized pixel processing", Optics and Laser Technology, 181, 111644 (2025). CrossRef T. Kozacki, J. Martinez-Carranza, R. Kukolowicz, and W. Finke, "Accurate reconstruction of horizontal parallax-only holograms by angular spectrum and efficient zero-padding", Appl. Opt. 59, 8450-8458 (2020). CrossRef T. Kozacki and K. Falaggis, "Angular spectrum method with compact space–bandwidth: generalization and full-field accuracy", Appl. Opt. 55, 5014 (2016). CrossRef T. Kozacki, M.S. Idicula, J. Martinez-Carranza, M. Chlipala, and R. Kukolowicz, "Non-uniform Fourier domain stretching method for ultra-wide-angle wave propagation", Opt. Laser Technol., 192, 113876 (2025). CrossRef S.F. Lin, M.F. Yin, J. Zhao, L. Rong, Y. Wang and D. Wang, "A novel hologram calculation method for large field-of-view scenarios", Opt. Laser Technol., 192, 113807 (2025). CrossRef G. Strang, Computational Science and Engineering, (Wellesley-Cambridge Press 2007). CrossRef T. Kozacki, J. Martinez-Carranza, I. Gerej, R. Kukolowicz, M. Chlipala, and M.S. Idicula, "Frequency domain method for wide angle computer generated hologram", Opt. Laser Technol., 181, 111610 (2025). CrossRef